Musical Expression of Islamic Identity: The Syncretism of Blangikhan Ritual in Lampung - Aryandari, Citra; Chaniago, Delsi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
The Blangikhan ritual underscores the significance of dignity within Lampung's culture, where the community is renowned for its hospitality and compassion towards one another. Blangikhan is a celebration and reflects community values, norms, and beliefs. This study aims to comprehend and explore the intertwined musical practices in the Blangikhan tradition of the Lampung community's religious and cultural identity. The researcher explores the correlation between the music produced in the Blangikhan tradition and the strengthening of Islamic identity among the community. The research utilized an ethnographic method. The data collection techniques were observation, interview, literature study, and documentation. The result concludes that music is an integral component of this event and reflects the Islamic Identity within Lampung's culture. The music in this ritual encompasses various genres, including Hadrah music, a religious musical tradition with sholawat lyrics, the music accompanying the Bedana dance that blends Malay-Islamic nuances, and even pop music with religious themes. This research delves deeper into how music in the Blangikhan ritual mirrors the Islamic identity and how the Lampung community incorporates Islamic elements into their performing arts. The study also considers how the production of this music influences the representation of Islamic identity within the Blangikhan ritual. This research holds significant relevance in comprehending how culture and religion can interact and shape identity within a cultural ritual context.